Vision and space in Tacitus - Myers, Matthew S. (2018)
This thesis explores the role of vision and space in the works of Tacitus. A number of recent studies have assessed the importance of vision, space, and the gaze in ancient literature, across a variety of different authors. The gaze in epic poetry has been analysed by Leigh (1997), Smith (2005), and Lovatt (2013); Feldherr (1998) has considered the role of spectacle in Livy; and Purves (2010) and Rimell (2015) have examined the role of space in Greek literature and Roman poetry respectively. Yet there has been no substantial study of these themes in Tacitus. The present work addresses this gap in scholarship by providing a wide ranging survey of visuality across the Tacitean corpus which extends from the gaze of the emperor and other individuals, to the collective gaze of the Roman populace and the gaze of the reader; within settings such as the dining room, the senate house, the city, and the battlefield. In considering this diverse material, I highlight the importance of taking a wide-ranging approach to the study of Tacitus’ visual techniques, emphasising the interrelation between disparate strands of Tacitean visuality. Such an eclectic approach reveals the centrality of vision and space to Tacitus’ ideas of power, control, corruption, and manipulation under the early principate, as well as the inherent ambiguity of Tacitus’ conception of the gaze.